Zinc Therapy for Wilson Disease in Children in French Pediatric Centers. Issue 6 (December 2015) - Santiago, Raoul; Gottrand, Frédéric; Debray, Dominique; Bridoux, Laure; Lachaux, Alain; Morali, Alain; Lapeyre, Delphine; Lamireau, Thierry
ABSTRACT: Background and Aims: Zinc therapy is considered a good option in Wilson disease (WD), as a first-line treatment in presymptomatic children and a maintenance therapy after the initial chelator therapy. The aim of the study was to determine the practical use of zinc treatment in French pediatric centers. Methods: A national survey was conducted in the 6 French centers using zinc acetate to treat WD. Clinical and biological parameters, dosage, and outcome were recorded. Results: A total of 26 children were reported to be treated with zinc acetate, alone or in association with chelators. Of the 9 children (35%) who received zinc alone as a first-line therapy, 2 were switched to D-penicillamine because of inefficacy and 7 remained on zinc alone, but serum transaminase levels normalized in only 4 of them. Five children (19%) were initially treated with zinc in association with D-penicillamine (n = 4) or Trientine (n = 1) with good efficacy. Among the 12 children (46%) who received zinc as a maintenance therapy after D-penicillamine, no relapse of hepatic cytolysis occurred during a median follow-up of 5.2 years, but 2 of them were switched to Trientine because of zinc-related adverse effects. Epigastric pain was observed in 4 children, and a gastric perforation occurred in 1 child. Conclusions: The present study demonstrates poor efficacy of zinc as first-line therapy to control liver disease in half presymptomatic children and a high incidence of related gastrointestinal adverse effects in children with WD.